Tunable structure and dynamics of solid electrolyte interphase at lithium metal anode. (September 2020) - Lang, Shuang-Yan; Shen, Zhen-Zhen; Hu, Xin-Cheng; Shi, Yang; Guo, Yu-Guo; Jia, Fei-Fei; Wang, Fu-Yi; Wen, Rui; Wan, Li-Jun
Abstract: Interfacial processes of lithium (Li) deposition and solid electrolyte interphase (SEI) formation are key determinants of the safety and performance in high-energy Li metal batteries. With the vigorous growth of effective strategies for stabilizing the interfaces, high-resolution and in situ characterization techniques are contemporaneously needed for probing and regulating the underlying mechanisms of these two processes and their interrelation. Therefore, we introduce in situ atomic force microscopy (AFM) that enables direct observation of the nanoscale morphology and dynamic evolution of the Li/electrolyte interfaces in working environments. Inhomogeneous SEI with nanoparticles (NPs) forms in traditional electrolyte, which extends with chain-like wrinkles as dendrite nucleates. By precisely controlling the concentration of lithium nitrate additive, we construct a compact bilayer SEI with a thin amorphous film covering a NP-packed layer structurally, promoting the uniform Li dissolution/deposition. This in situ AFM visualization in Li metal batteries highlights direct insights into distinct nanostructures and growth dynamics of nitrate-mediated SEI film at Li anode, and provides a universal and convenient technique for interfacial analysis and mechanistic understanding of Li metal anodes. Graphical abstract: Direct insights into the nanoscale SEI evolution at Li anode are provided inside working batteries using in situ AFM. LiNO3 presents straightforward SEI regulation. Compact bilayer SEI is built in 5.0 wt% LiNO3 electrolyte, however inhomogeneous one in 1.0 wt%. Noticeably, SEI on dendritic tip extends with radical chain-like wrinkles, revealing different dynamic features at surfaces/dendrites. Image 1 Highlights: In situ AFM visualization present nanoscale SEI dynamics at Li metal anode. LiNO3 shows regulating effect on initial SEI formation, with a fine-structured bilayer one in 5.0 wt%. SEI wrinkle feature is monitored on dendritic tip, revealing site-dependent interfacial evolution.